IDH1 and IDH2 Mutations in Colorectal Cancers. Issue 5 (30th April 2021) - Huang, Jialing; Tseng, Li-Hui; Parini, Vamsi; Lokhandwala, Parvez M; Pallavajjala, Aparna; Rodriguez, Erika; Xian, Rena; Chen, Liam; Gocke, Christopher D; Eshleman, James R; Lin, Ming-Tseh
Abstract: Objectives: To elucidate clinicopathologic and molecular characteristics of IDH1 and IDH2 ( IDH1/2 ) mutations in colorectal cancers (CRCs). Methods: We evaluated IDH1 / 2 mutations in 1, 623 CRCs using a next-generation sequencing assay. Results: IDH1 / 2 mutations, predominantly IDH1 p.R132C, were detected in 15 (0.9%) CRCs and in 5 (3.0%) of 167 BRAF p.V600E–mutated CRCs. Three IDH1/2 -mutated CRCs were associated with inflammatory bowel disease. They were significantly associated with old age, mucinous or signet ring cell adenocarcinoma, and high-grade histomorphology. Concordance of variant allele frequency between IDH1 / 2 mutants and other trunk drivers in CRCs and presence of IDH1/2 mutation in the adenoma and early adenocarcinoma indicated IDH1/2 mutations could be trunk drivers suitable for targeted therapy. Conclusions: IDH1 / 2 mutations in CRCs were uncommon but enriched in BRA F p.V600E–mutated CRCs and perhaps colitis-associated CRCs. Further studies on IDH1 / 2- mutated CRCs are needed to clarify their clinicopathologic features and implications for targeted therapy.